ANALISIS PENGARUH BAURAN PEMASARAN DAN KUALITAS PELAYANAN TERHADAP WORD OF MOUTH MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA “DIMENSI KOPI” TRAWAS - Cahyanti, Dita Dwi; Prasetyo, Indra; Utari, Woro (Prodi Magister Manajemen Universitas Wijaya Putra, 2023)
The purpose of this research is to find out and analyze the effect of marketing mix and service quality on word of mouth both directly and through customer satisfaction. This research is an explanatory research with quantitative approach. The population in this study were customers of Coffee Dimensions over the age of 15 years totaling 150 people. The number of samples taken in this study were 150 consumers using non probality sampling techniques. The results of research and data analysis show that the marketing mix has an effect on customer satisfaction, service quality has an effect on customer satisfaction, marketing mix has an effect on word of mouth, service quality has an effect on word of mouth, customer satisfaction has an effect on word of mouth, the marketing mix has an effect on word of mouth through customer satisfaction, and service quality affect word of mouth through customer satisfaction.